2020
DOI: 10.1001/jama.2020.2901
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Types, and Sources of Bullying Reported by US General Surgery Residents in 2019

Abstract: infection-control/controlrecommendations.html 4. Verbeek JH, Rajamaki B, Ijaz S, et al. Personal protective equipment for preventing highly infectious diseases due to exposure to contaminated body fluids in healthcare staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
55
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 5 publications
(20 reference statements)
1
55
1
4
Order By: Relevance
“…1,4,5,10,11 At work, women physicians may spend more time with patients and more frequently address psychosocial issues. [12][13][14][15] At home, women physicians also spend more time on both household and childcare activities and on completing work from home. [16][17][18] This combination of increased burdens for women vs men physicians both at work and at home may explain much of the observed gender disparities in WLI.…”
Section: Introductionmentioning
confidence: 99%
“…1,4,5,10,11 At work, women physicians may spend more time with patients and more frequently address psychosocial issues. [12][13][14][15] At home, women physicians also spend more time on both household and childcare activities and on completing work from home. [16][17][18] This combination of increased burdens for women vs men physicians both at work and at home may explain much of the observed gender disparities in WLI.…”
Section: Introductionmentioning
confidence: 99%
“…Workplace mistreatment (eg, discrimination, harassment, abuse, and assault) and its institutional responses are associated with hostile work environments for physicians. 1 , 2 , 3 , 4 The prevalence of workplace mistreatment has previously been shown to vary by gender and race/ethnicity, with the highest rates among women and racial/ethnic minority populations. 5 , 6 Prior research has suggested that workplace mistreatment increases feelings of marginalization and may threaten a person’s sense of self, resulting in decreased job performance and productivity as well as increased stress, job dissatisfaction, negative workplace behaviors, and turnover.…”
Section: Introductionmentioning
confidence: 99%
“…These challenges can further be exacerbated by bullying in the surgical environment which has previously been documented and defined as persistent negative behaviour or aggression, and is often experienced more by women. 15,16 In our study, 17% of participants were verbally discouraged from pursuing a career in surgery, mostly by male colleagues and 36% of participants reported a negative experience, both of which can be considered as bullying. This form of mistreatment can be mitigated through training focused on professionalism.…”
Section: Discussionmentioning
confidence: 61%